UJI TAK MERUSAK (NDT) DIESEL STORAGE TANK DENGAN METHODE MAGNETIC PARTICLE INSPECTION - Fadilah, Fadil; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Oil and gas business activities are high-cost and high-risk activities, therefore it is necessary to carefully calculate all existing aspects. Directorate General of Oil and Gas c.q. The Directorate of Oil and Gas Engineering and Environment has the task of ensuring the feasibility of using an equipment so as to create a safe and appropriate installation for use in oil and gas operations. The drilling tower is one of the main components in oil and gas drilling activities. For this reason, it is necessary to carry out inspections to ensure the quality of the towers produced so that they comply with existing standards and are safe to use. Magnetic Particle Inspection (MPI) is one of the Non-Destructive Test (NDT) methods to carry out inspections to ensure that equipment, especially towers, are in a safe and suitable condition for use. By ensuring the safety and feasibility of the tower as a supporting component of a drilling installation, it can be concluded that its safety and feasibility can be concluded.